Composition, processing method of back-filling fire prevention section penetration part
The composition of a binder material, thermally expandable graphite, polyphosphate metal salt compounds, and other inorganic compounds addresses the challenges of refractory materials by enhancing workability, thermal expansion, and shape stability, while ensuring strength and crack resistance after drying.
Patent Information
- Application Number
- JP2023159232
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-09-22
AI Technical Summary
Existing refractory materials face challenges in filling gaps in combustion areas, maintaining shape stability after heating, and ensuring adequate workability and strength after drying, while also dealing with processability issues related to thermal expansion and water content.
A composition comprising a binder material, thermally expandable graphite, a polyphosphate metal salt compound, and other inorganic compounds, with specific mass ratios that enhance workability, thermal expansion, shape stability, strength after drying, and crack resistance.
The composition maintains sufficient workability and shape stability after combustion, exhibits excellent strength and crack resistance after drying, and balances thermal expansion with processability, addressing the limitations of previous refractory materials.
Smart Images

Figure 2025050436000001 
Figure 2025050436000002 
Figure 2025050436000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition and a method for backfilling a fire compartment penetration. [Background technology]
[0002] 2. Description of the Related Art It is known to provide fireproofing to walls, floors, etc. of buildings by coating or filling them with a fireproof material (fireproof composition). As such a fireproof material, a non-expanding putty-like fireproof material containing water, an inorganic filler, a thickener, and a binder is used (see Patent Document 1).
[0003] In addition, a thermally expandable putty composition using thermally expandable graphite is used as a putty-like fire-resistant material that can seal gaps that occur when pipes are deformed or cable coating materials are burned during a fire (see Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-050118 [Patent Document 2] Patent Publication No. 2022-082191 Summary of the Invention [Problem to be solved by the invention]
[0005] In the case of the non-expanding refractory material as described in Patent Document 1, there was a problem that the gaps in the combustion area could not be filled. In addition, the refractory material filled after heating and combustion became brittle and easily crumbled, and the filling properties could not be maintained. In the case of a thermal expansion type fireproof material using thermal expansion graphite or vermiculite as a thermal expansion material as in Patent Document 2, the aspect ratio of the thermal expansion material is large and bulky, so that the workability of the putty composition before drying may decrease as the amount added increases depending on the usage environment, and there was a demand for further compatibility between thermal expansion and workability. In addition, simply increasing the amount of water to solve this demand increases shrinkage during drying, causing problems such as cracks occurring after drying and weakening the strength after drying.
[0006] The present invention has been made in consideration of the above circumstances, and provides a composition that has excellent processability, strength after drying, and crack resistance after drying, while maintaining sufficient workability, thermal expandability, and shape stability after combustion. [Means for solving the problem]
[0007] According to the present invention, there is provided a composition comprising a binder material, thermally expandable graphite, a metal polyphosphate compound, and an inorganic compound other than the binder material, the thermally expandable graphite, and the metal polyphosphate compound, wherein the proportions of each component when the total of the four components, i.e., the binder material, the thermally expandable graphite, the metal polyphosphate compound, and the other inorganic compound, is taken as 100% by mass, are 0.5 to 20.0% by mass of the binder material, 0.3 to 45.0% by mass of the thermally expandable graphite, 0.5 to 50.0% by mass of the metal polyphosphate compound, and 6.0 to 97.7% by mass of the other inorganic compound.
[0008] As a result of extensive research, the present inventors have found that a composition containing the above-mentioned components in the above-mentioned ratios can solve the above problems, leading to the completion of the present invention.
[0009] [1] A composition comprising a binder material, thermally expandable graphite, a metal polyphosphate compound, and an inorganic compound other than the binder material, the thermally expandable graphite, and the metal polyphosphate compound, wherein the proportions of each of the four components, i.e., the binder material, the thermally expandable graphite, the metal polyphosphate compound, and the other inorganic compound, taken as 100% by mass in total are 0.5 to 20.0% by mass of the binder material, 0.3 to 45.0% by mass of the thermally expandable graphite, 0.5 to 50.0% by mass of the metal polyphosphate compound, and 6.0 to 97.7% by mass of the other inorganic compound. [2] The composition described in [1], wherein the binder material is a hydrophilic polymer. [3] The composition according to [1] or [2], wherein water is contained in an amount of 20 to 70% by mass based on 100% by mass of the composition. [4] A method for backfilling a fire compartment penetration, comprising a construction step of using the composition according to any one of [1] to [3]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] 1. Composition of the composition The composition of the present invention contains a binder material, thermally expandable graphite, a metal polyphosphate compound, and an inorganic compound other than the binder material, the thermally expandable graphite, and the metal polyphosphate compound. The composition of the present invention is a composition with excellent processability, and can be used as a putty that can be deformed to fit a shape. The composition can be provided as a thermally expandable composition or a putty-like thermally expandable composition.
[0011] <Binder materials> The binder material is a material that acts as a binding agent to bind the components of the composition together, and there are organic compound binders and inorganic compound binders.
[0012] <Organic compound binder> The organic compound binder is a binding agent made of an organic compound, and by mixing an appropriate amount, the composition can be made to have a hardness suitable for application. The organic compound binder may be used alone or in combination of two or more kinds. In addition, an inorganic compound binder may be used in combination.
[0013] The organic compound binder is preferably a hydrophilic polymer. Examples of the hydrophilic polymer include water-soluble polymers that are soluble in water and water-absorbent polymers that can absorb water and expand, and specific examples of such polymers include starch, cellulose derivatives, polyvinyl alcohol, modified acrylic acid ester copolymers, polyethylene oxide, polypropylene oxide, ethylene oxide-propylene oxide copolymers, ethylene oxide-propylene oxide-phenyl glycidyl ether copolymers, ethylene oxide-propylene oxide-allyl glycidyl ether copolymers, and sodium alginate.
[0014] Examples of cellulose compounds include carboxymethylcellulose, methylcellulose, hydroxyethylcellulose, and derivatives thereof such as salts. Examples of carboxymethylcellulose salts include sodium carboxymethylcellulose and ammonium carboxymethylcellulose salts. Examples of modified acrylic acid ester copolymers include crosslinked products of sulfoethylacrylate-acrylamide-acrylic acid copolymer sodium salt.
[0015] <Inorganic compound binder> The inorganic compound binder is a binding agent made of an inorganic compound, and by blending an appropriate amount of it, the composition can be made to have a hardness suitable for application.
[0016] Such inorganic compound binders may be naturally derived or chemically synthesized, and are not particularly limited, but examples thereof include layered silicate minerals, fibrous silicate minerals, etc. The inorganic compound binders may be used alone or in combination of two or more. In addition, organic compound binders may be used in combination.
[0017] The layered silicate mineral is not particularly limited, but examples thereof include smectite clay minerals such as smectite, bentonite, montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, hectorite, and stevensite; sericite, illite, glauconite, chlorite, and talc. Among them, it is preferable to include at least one selected from the group consisting of bentonite, montmorillonite, smectite, and hectorite, and more preferably to include at least one of bentonite and smectite. These may be used alone or in combination of two or more.
[0018] Examples of fibrous silicate minerals include sepiolite, palygorskite, etc. Among these, it is preferable to include at least sepiolite. These may be used alone or in combination of two or more.
[0019] Other examples of inorganic compound binders include amorphous clay minerals such as imogolite and allophane, porous aluminosilicates such as zeolite, water glass, etc. These may be used alone or in combination of two or more.
[0020] When the total of the binder material, the thermally expandable graphite, the metal polyphosphate compound, and the inorganic compound other than the binder material, the thermally expandable graphite, and the metal polyphosphate compound (hereinafter referred to as "four components") is taken as 100 mass%, the ratio of the binder material is 0.5 to 20.0 mass%, preferably 0.7 to 14.0 mass%, and more preferably 0.8 to 7.0 mass%. If the ratio of the binder material is too small, the putty composition may be too soft, resulting in insufficient processability or workability. If the ratio of the binder material is too large, the putty composition may be too hard, resulting in insufficient processability. The proportion of the binder material is specifically, for example, 0.5, 0.7, 0.8, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, or 20.0 mass%, and may be within a range between any two of the numerical values exemplified here.
[0021] <Thermal expandable graphite> Thermally expandable graphite is a crystalline compound that is obtained by surface-treating graphite powder such as natural graphite or pyrolytic graphite with an inorganic acid such as sulfuric acid or nitric acid, and a strong oxidizing agent such as concentrated nitric acid or permanganate, and that maintains a graphite layer structure. When exposed to a temperature equal to or higher than the expansion start temperature (about 200°C) under normal pressure, it thermally expands by 100 times or more. The graphite powder such as natural graphite or pyrolytic graphite may be deoxidized or further neutralized.
[0022] When the total of the above four components is 100 mass%, the ratio of the thermally expandable graphite is 0.3 to 45.0 mass%, preferably 0.7 to 30.0 mass%, and more preferably 0.8 to 15.0 mass%. If the ratio of the thermally expandable graphite is too small, the thermal expansion may be insufficient. If the ratio of the thermally expandable graphite is too large, the processability and shape stability after thermal expansion may be poor. The ratio of the thermally expandable graphite is specifically, for example, 0.3, 0.7, 0.8, 1.0, 5.0, 10.0, 15.0, 20.0, 25.0, 30.0, 35.0, 40.0, or 45.0 mass%, and may be within a range between any two of the numerical values exemplified here.
[0023] <Metal polyphosphate compounds> In the present invention, it is preferable to contain a metal polyphosphate compound in order to improve processability. The metal polyphosphate compound plays a role in softening the hardness of the putty composition before drying without increasing the amount of water, and also imparts shape stability after burning. These may be used alone or in combination of two or more.
[0024] Examples of the metal polyphosphate compound include sodium tripolyphosphate, sodium pentapolyphosphate, sodium tetrapolyphosphate, and potassium tripolyphosphate.
[0025] When the total of the above four components is 100% by mass, the ratio of the polyphosphate metal salt compound is 0.5 to 50.0% by mass, preferably 2.0 to 35.0% by mass, and more preferably 3.0 to 20.0% by mass. If the ratio of the polyphosphate metal salt compound is too small, the putty composition may become too hard, resulting in poor processability and shape stability after burning. If the ratio of the polyphosphate metal salt compound is too large, the putty composition may become too soft, resulting in poor processability and thermal expansion. The ratio of the polyphosphate metal salt compound is specifically, for example, 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 10.0, 15.0, 20.0, 25.0, 30.0, 35.0, 40.0, 45.0, or 50.0% by mass, and may be within a range between any two of the numerical values exemplified here.
[0026] In addition, when the other inorganic compounds are taken as 100 parts by mass, the content of the polyphosphate metal salt compound is preferably 2.1 to 55.6 parts by mass, more preferably 3.2 to 25.6 parts by mass. This range provides an excellent balance between processability and shape stability after combustion. The content of the polyphosphate metal salt compound is, for example, 2.1, 2.5, 3.0, 3.2, 3.5, 4.0, 5.0, 10.0, 15.0, 20.0, 25.0, 30.0, 35.0, 40.0, 45.0, 50.0, 55.0, or 55.6 parts by mass relative to 100 parts by mass of the other inorganic compounds, and may be within a range between any two of the numerical values exemplified here.
[0027] <Other inorganic compounds> The shape of the inorganic compound other than the binder material, the thermally expandable graphite, and the metal polyphosphate compound may be, for example, spherical, elliptical, cubic, rectangular, or random, and may be hollow or solid. The average particle size of the particulate inorganic compound is, for example, 10 to 1000 μm, preferably 20 to 800 μm, more preferably 30 to 500 μm, and even more preferably 40 to 200 μm. The "average particle size" refers to the particle size at an integrated value of 50% in the particle size distribution determined by a laser diffraction / scattering method. These may be used alone or in combination of two or more.
[0028] Examples of other inorganic compounds include metal oxides such as alumina, silica, aluminosilicate, zinc oxide, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, and ferrites; hydrated inorganic substances such as calcium hydroxide, magnesium hydroxide, aluminum hydroxide, and hydrotalcite; metal carbonates such as basic magnesium carbonate, calcium carbonate, magnesium carbonate, zinc carbonate, strontium carbonate, and barium carbonate; calcium salts such as calcium sulfate and calcium silicate; glass beads, silica-based balloons, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon balloons, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, zinc borate, various magnetic powders, fly ash, inorganic hollow fillers, perlite, obsidian, perlite, rosin, diatomaceous earth, dehydrated sludge, boron, sodium tetraborate hydrate (borax), and phosphate compounds.
[0029] <Phosphate compounds> Phosphate compounds include, in addition to phosphoric acid compounds, phosphorous acid compounds, hypophosphorous acid compounds, metaphosphate compounds, pyrophosphate compounds, and non-metallic polyphosphate compounds.
[0030] Examples of phosphate compounds include aluminum monophosphate, sodium monophosphate, potassium monophosphate, calcium monophosphate, zinc monophosphate, aluminum diphosphate, sodium diphosphate, potassium diphosphate, calcium diphosphate, zinc diphosphate, aluminum triphosphate, sodium triphosphate, potassium triphosphate, calcium triphosphate, zinc triphosphate, magnesium triphosphate, ammonium monophosphate, ammonium diphosphate, tricalcium phosphate, aluminum phosphate, etc.
[0031] Examples of the phosphite compounds include aluminum phosphite, aluminum hydrogen phosphite, sodium phosphite, potassium phosphite, calcium phosphite, and zinc phosphite.
[0032] Examples of hypophosphite compounds include aluminum hypophosphite, sodium hypophosphite, potassium hypophosphite, calcium hypophosphite, and zinc hypophosphite.
[0033] Examples of metaphosphate compounds include aluminum metaphosphate, sodium metaphosphate, potassium metaphosphate, calcium metaphosphate, zinc metaphosphate, and sodium hexametaphosphate.
[0034] An example of the pyrophosphate compound is sodium pyrophosphate.
[0035] Examples of non-metallic polyphosphate compounds include ammonium polyphosphate and melamine-modified ammonium polyphosphate.
[0036] When the total of the above four components is 100 mass%, the ratio of the other inorganic compounds is 6.0 to 97.7 mass%, preferably 36.0 to 97.2 mass%, and more preferably 64.0 to 96.6 mass%. If the ratio of the inorganic compounds other than the binder material and the polyphosphate metal salt is too small, the strength after drying may be insufficient. If the ratio of the inorganic compounds other than the binder material and the polyphosphate metal salt compound is too large, the putty composition may become too hard and the processability may be insufficient. The proportion of other inorganic compounds is, for example, 6.0, 10.0, 15.0, 20.0, 25.0, 30.0, 35.0, 36.0, 40.0, 45.0, 50.0, 55.0, 60.0, 64.0, 65.0, 70.0, 75.0, 80.0, 85.0, 90.0, 95.0, 96.7, 97.2, or 97.7 mass%, and may be within a range between any two of the values exemplified here.
[0037] Other additives such as fibrous compounds, AE (Air Entraining) agents, preservatives, antifungal agents, antioxidants, softeners, tackifiers, etc. may be added as appropriate to the extent that the physical properties are not impaired.
[0038] <Fibrous compounds> The fibrous compound may be an inorganic fiber compound other than the binder material and an organic fiber compound, and may contain both an inorganic fiber compound and an organic fiber compound. The fibrous compound may have any shape as long as it is fibrous, and the cross-sectional shape of the fibrous compound may be, for example, a circle, an ellipse, or a polygon. The ratio L / D of the length L to the diameter D of the fibrous compound is, for example, more than 10, preferably 50 or more, and more preferably 100 or more. The upper limit of L / D is not particularly specified, but is, for example, 10,000. The diameter D of the fibrous compound is, for example, 1 to 100 μm, preferably 2 to 50 μm, and more preferably 5 to 20 μm. The length L of the fibrous compound is, for example, 0.05 to 10 mm, preferably 0.1 to 8 mm, and more preferably 0.2 to 5 mm.
[0039] Examples of inorganic fiber compounds other than binder materials include glass fibers (E glass fibers, C glass fibers, S glass fibers, D glass fibers), rock wool, ceramic fibers (silica alumina fibers, alumina fibers, silica fibers), zirconia fibers, carbon fibers, bulk alkaline earth silicate fibers, gypsum fibers, carbon fibers, metal fibers, slag fibers, and basalt fibers.
[0040] Examples of the organic fiber compound include meta-aramid fiber, para-aramid fiber, amide fiber, pulp fiber, cellulose fiber, polyparaphenylene benzobisoxazole fiber, polyarylate fiber, and the like.
[0041] The composition of the present invention preferably contains water from the viewpoint of facilitating the work when sealing gaps between pipes / cables and fire walls in buildings. When the composition contains water, the proportion of solids is preferably 30 to 80 mass%, more preferably 40 to 74 mass%. The water content is preferably 20 to 70 mass%, more preferably 26 to 60 mass%, based on 100 mass% of the composition. If the proportion of water is small (the solid content is high), the putty may become crumbly and have poor workability. If the proportion of water is large (the solid content is low), the putty may be too soft, resulting in poor workability, workability, and strength after drying, and may crack after drying. The water content may be, for example, 20, 25, 26, 30, 35, 40, 45, 50, 55, 60, 65, or 70% by mass, or may be within a range between any two of the values exemplified here.
[0042] The composition of the present invention can be used as a joint material to seal gaps between pipes, cables, and fire walls in buildings.
[0043] 2. Method for producing the composition The composition of the present invention can be produced by mixing and stirring the above four components, additives as required, and water using a mixer or the like.
[0044] 3. Backfilling method for fire compartment penetrations A method for backfilling a fire compartment penetration according to another aspect of the present invention is a method comprising a construction step using the above-mentioned composition.
[0045] In the above construction process, for example, the above-mentioned plastic composition is filled into gaps between a fire wall or the like serving as a fire compartment through which pipes and cables in a building penetrate, and the pipes and cables themselves. EXAMPLES
[0046] 1. Preparation of the Composition The components shown in Tables 1 to 5 were mixed and stirred using a mixer according to the compositions in the tables (units: mass%) to prepare compositions of the examples and comparative examples. Note that in the tables, the amounts of the binder material, thermally expandable graphite, metal polyphosphate compound, other inorganic compounds, and medium per 100 mass% (whole composition) are shown for the total of the four components of the binder material, thermally expandable graphite, metal polyphosphate compound, and other inorganic compounds, and for the medium, and further the amounts of the binder material, thermally expandable graphite, metal polyphosphate compound, and other inorganic compounds per 100 mass% of the above four components are shown.
[0047] [Table 1]
[0048] [Table 2]
[0049] [Table 3]
[0050] [Table 4]
[0051] [Table 5]
[0052] Details of the components in the table are as follows: <Binder materials> [Organic compound binders] Sodium carboxymethylcellulose: "Sodium carboxymethylcellulose" manufactured by Hayashi Pure Chemical Industries, Ltd. Modified polyacrylic crosslinked material: "AQUALIC CS6S" manufactured by Nippon Shokubai Co., Ltd. [Inorganic compound binder] Bentonite: "Akagi" manufactured by Hojun Co., Ltd.
[0053] <Thermal expandable graphite> Thermally expandable graphite: "SS-3" manufactured by Air Water Chemical Co., Ltd.
[0054] <Inorganic compounds> Aluminum hydroxide: "C-301N" manufactured by Sumitomo Chemical Co., Ltd. Calcium carbonate: "TA-004" manufactured by Chichibu Lime Industry Co., Ltd.
[0055] <Non-metallic polyphosphate compounds> Ammonium polyphosphate: HP-APP II, manufactured by SCM Industrial Chemical Co., Ltd. <Metal polyphosphate compounds> Sodium tripolyphosphate: "Sodium tripolyphosphate" manufactured by Taihei Chemical Industry Co., Ltd. Sodium tetrapolyphosphate: "Sodium tetrapolyphosphate" manufactured by Taihei Chemical Industry Co., Ltd. Potassium tripolyphosphate: "Potassium tripolyphosphate" manufactured by Taihei Chemical Industry Co., Ltd.
[0056] <Various evaluations> The compositions of the Examples and Comparative Examples were subjected to various evaluations as shown below. The results are shown in Tables 1 to 5.
[0057] <Workability> The compositions of the Examples and Comparative Examples before drying were subjected to a softness measurement at a load of 150 g and a temperature of 21° C. in accordance with JIS A5752. A specified cone was inserted vertically into the test piece, and the penetration depth was measured to the nearest 0.1 mm. Then, the processability was evaluated according to the following evaluation criteria based on the penetration depth. [Evaluation Criteria] ◎: The penetration depth is 170 [1 / 10 mm] or more but less than 230 [1 / 10 mm]. ○: Penetration depth is 140 [1 / 10 mm] or more and less than 170 [1 / 10 mm]; Or, it is greater than or equal to 230 [1 / 10 mm] and less than 260 [1 / 10 mm]. △: Penetration depth is 110 [1 / 10 mm] or more and less than 140 [1 / 10 mm]; Or, it is greater than or equal to 260 [1 / 10 mm] and less than 290 [1 / 10 mm]. ×: The penetration depth is less than 110 [1 / 10 mm] or 290 [1 / 10 mm] or more.
[0058] <Workability (non-stickiness to gloves)> Wearing latex gloves, participants gripped 100 g of the undried compositions of the Examples and Comparative Examples 10 times, and then measured the weight of the residue on the gloves. The weight of the residue was calculated based on the following formula. Based on the weight of the residue, the non-adhesiveness was evaluated according to the following criteria. Weight of deposit [g] = (weight of glove after squeezing the composition 10 times) - (original weight of glove) [Evaluation Criteria] ⊚: The weight of the attached matter is less than 0.1 g. ◯: The weight of the deposit is 0.1 g or more and less than 0.4 g. △: The weight of the attached matter is 0.4 [g] or more and less than 0.7 [g]. ×: The weight of the attached matter is 0.7 g or more.
[0059] <Crack resistance after drying> Using the compositions of the Examples and Comparative Examples before drying, test pieces of 100 mm length × 100 mm width × 100 mm height were prepared and dried at 110° C. for 7 days. The number of cracks of 30 mm or more was then visually observed and rated according to the following criteria. [Evaluation Criteria] ◎: No cracks. ○: Cracks were confirmed, and there were three or less cracks of 30 mm or more. △: There are four cracks of 30 mm or more. ×: There are 5 or more cracks of 30 mm or more.
[0060] <Strength after drying> Using the compositions of the examples and comparative examples before drying, test pieces of 30 mm long x 30 mm wide x 4 mm thick were prepared, and these were dried at 110°C for 24 hours to obtain test pieces of the compositions after drying. The test pieces after drying were broken at a compression speed of 50 mm / min using a three-point bending test jig (upper pushing side tip R1 mm and width 80 mm, lower two-point support side R1 mm, width 80 mm, support distance 20 mm) to measure the strength (three-point bending fracture strength). Then, based on the three-point bending fracture strength, the shape stability after drying was evaluated according to the following evaluation criteria. [Evaluation Criteria] ◎: Three-point bending breaking strength is 40 [N] or more. ◯: The three-point bending breaking strength is 30 [N] or more and less than 40 [N]. △: The three-point bending breaking strength is 20 [N] or more and less than 30 [N]. ×: The three-point bending breaking strength is less than 20 [N].
[0061] <Thermal expansion> Using the compositions before drying of the examples and comparative examples, test pieces of 30 mm length x 30 mm width x 4 mm thickness were prepared, and these were dried under conditions of 110°C for 24 hours to obtain test pieces of the dried compositions. The dried test pieces were then left in an atmosphere maintained at 300°C for 0.5 hours, after which their volumes were measured, and the expansion ratios were calculated from the volumes. Based on the volume expansion ratios, the thermal expandability was evaluated according to the following evaluation criteria. [Evaluation Criteria] ⊚: The volume expansion ratio is 2.0 times or more. ◯: The volume expansion ratio is 1.6 times or more and less than 2.0 times. △: The volume expansion ratio is 1.3 times or more and less than 1.6 times. ×: The volume expansion ratio is less than 1.3 times.
[0062] <Shape stability after thermal expansion> Using the compositions before drying of the examples and comparative examples, test pieces of 30 mm long x 30 mm wide x 4 mm thick were prepared, and these were dried at 110 ° C for 24 hours to obtain test pieces of the dried compositions. The dried test pieces were left in an atmosphere maintained at 300 ° C for 0.5 hours, and then a three-point bending test jig (upper pushing side tip R1 mm and width 80 mm, lower two-point support side R1 mm, width 80 mm, support distance 20 mm) was used to measure the strength (three-point bending fracture strength) when the test pieces were broken under the condition of a compression speed of 50 mm / min. Here, the higher the three-point bending fracture strength, the higher the strength after thermal expansion. Then, based on the three-point bending fracture strength, the shape stability after thermal expansion was judged according to the following evaluation criteria. [Evaluation Criteria] ⊚: Three-point bending breaking strength is 1.5 [N] or more. ◯: The three-point bending breaking strength is 1.0 [N] or more and less than 1.5 [N]. △: The three-point bending breaking strength is 0.5 [N] or more and less than 1.0 [N]. ×: The three-point bending breaking strength is less than 0.5 [N].
Claims
1. A binder material; Thermally expandable graphite; A metal polyphosphate compound; an inorganic compound other than the binder material, the thermally expandable graphite, and the metal polyphosphate compound; A composition comprising: The ratio of each component when the total of the four components, namely, the binder material, the thermally expandable graphite, the metal polyphosphate compound, and the other inorganic compound, is 100 mass %, is 0.5 to 20.0% by weight of the binder material; 0.3 to 45.0% by mass of the thermally expandable graphite, 0.5 to 50.0% by mass of the metal polyphosphate compound, 6.0 to 97.7% by mass of the other inorganic compound, The composition.
2. The composition of claim 1 , wherein the binder material is a hydrophilic polymer.
3. The composition according to claim 1, wherein the composition contains 20 to 70% by mass of water based on 100% by mass of the composition.
4. A method for backfilling a fire compartment penetration, comprising a construction step of using the composition according to any one of claims 1 to 3.
Citation Information
Patent Citations
Refractory member and its construction method
JP2008184896A
Fire compartment penetrating part structure and method of constructing the same
JP2009197476A
Electric fusion joint and connection structure
JP2021089000A
Fire-resistant heat insulating sheet
JP2021121493A
Laminate
WO2023163133A1